Wearable inertial sensors and pressure MAT detect risk factors associated with ACL graft failure that are not possible with traditional return to sport assessments. Issue 1 (2nd July 2019) - Dan, Michael J; Lun, Kimberly Kai; Dan, Luke; Efird, Jimmy; Pelletier, Matthew; Broe, David; Walsh, William R
Abstract : Introduction: Anterior cruciate ligament reconstruction (ACLR) is associated with poor return to sport and high graft re-rupture rates. This study explored the use of a wearable inertial sensor (ViMove) that incorporates an accelerometer and gyroscope, and MatScan pressure sensing mat (TekScan, South Boston, Massachusetts, USA) to provide objective return-to-sport measures. Methods: Three cohorts' ACLR patients, non-athletic controls and elite athletes (Australian seven's rugby Olympic Gold medallist). Patients performed biometric and functional tests (thigh circumference and triple hop) and the ViMove knee module (consisting of single and double leg squats, hops and box drops) for lower limb alignment assessment, concurrently with force plate. Results: Elite athletes had less varus/valgus (VV) movement during ViMove exercises compared with the ACLR cohort, who in turn had less VV malalignment than controls. When analysing side-to-side differences, single leg squats and box drop were asymmetrical in the ACL group, with greater malalignment in the reconstructed leg (p<0.05). Subgroup analysis failed to differentiate who passed or failed current return to sport assessment. TekScan pressure plate detected differences in double leg landing and flight time while hopping not detected with ViMove, suggesting ACL patients compensate by offloading the reconstructed leg to improve coronal alignment during double leg activity. Conclusion: The inertial sensor detected differences in motion for patients following ACLR, which are known to be associated with graft rupture and were not detected with functional return to sport testing. Coupling the device with data from a pressure plate provides a powerful assessment tool detecting alignment differences known to be associate with graft failure only previously detected in formal gait analysis.